THE INFLUENCE OF COVERAGE ATTRIBUTES ON COMMUNAL FARMERS’ WILLINGNESS TO ADOPT CATTLE INSURANCE IN LUPANE DISTRICT, ZIMBABWE - Nyakuchena, Nyasha; Musara, Joseph.P; Zivenge, Emmanuel (Applied Studies in Agribusiness and Commerce, 2025)
This study examines the role of coverage attributes specifically, their scope, clarity, and relevance in influencing the willingness of communal farmers to adopt cattle insurance. The research was guided by the Stakeholder Networking Theory. Employing a mixed-methods approach in Lupane District, Zimbabwe, the research utilized a sample of 219 communal farmers, selected via multistage sampling for quantitative data, and 25 key informants, selected using purposive sampling for qualitative data. The Probit regression analysis revealed a statistically significant positive coefficient of 0.242 (p<0.001) for the relationship between Coverage Attributes and Willingness to Adopt. This indicates that farmers’ decisions are significantly driven by the comprehensiveness of covered risks and the simplicity of the policy’s terms. The findings highlight that existing products fail to meet farmer expectations regarding risk coverage and ease of understanding. This study concludes that insurance schemes must be designed to be both comprehensive and user-friendly, providing practical insights for creating policies that are genuinely attractive and relevant to the specific needs of this vulnerable demographic.